2020
DOI: 10.1111/bjet.12993
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal data capabilities for learning: What can multimodal data tell us about learning?

Abstract: Most research on learning technology uses clickstreams and questionnaires as their primary source of quantitative data. This study presents the outcomes of a systematic literature review of empirical evidence on the capabilities of multimodal data (MMD) for human learning. This paper provides an overview of what and how MMD have been used to inform learning and in what contexts. A search resulted in 42 papers that were included in the analysis. The results of the review depict the capabilities of MMD for learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(72 citation statements)
references
References 94 publications
2
60
0
Order By: Relevance
“…To address this, MMLA research focuses on the use of physical sensors, due to their capacity to capture physiological and behavioural manifestations of learners’ emotions and traits that cannot be easily seen by the human naked eye such as learners’ emotions, gaze, cognitive states and bodily responses. For instance, recent work in MMLA has enabled performing text, speech, handwriting, sketch, gesture, affect, or eye‐gaze analysis (eg, Blikstein & Worsley, 2016; Sharma & Giannakos, 2020; Spikol, Ruffaldi, Dabisias, & Cukurova, 2018), in order to extract indicators and use these to model higher‐order cognitive, meta‐cognitive and affective factors for research purposes or to provide automated feedback to enable learner reflections (eg, Ochoa et al ., 2018). As it appears in this special issue, Sharma and Giannakos (2020) summarise the state‐of‐the‐art in various learning capacities of multimodal data as well as the critical insights about MMLA in the form of a systematic literature review.…”
Section: The Promisementioning
confidence: 99%
See 1 more Smart Citation
“…To address this, MMLA research focuses on the use of physical sensors, due to their capacity to capture physiological and behavioural manifestations of learners’ emotions and traits that cannot be easily seen by the human naked eye such as learners’ emotions, gaze, cognitive states and bodily responses. For instance, recent work in MMLA has enabled performing text, speech, handwriting, sketch, gesture, affect, or eye‐gaze analysis (eg, Blikstein & Worsley, 2016; Sharma & Giannakos, 2020; Spikol, Ruffaldi, Dabisias, & Cukurova, 2018), in order to extract indicators and use these to model higher‐order cognitive, meta‐cognitive and affective factors for research purposes or to provide automated feedback to enable learner reflections (eg, Ochoa et al ., 2018). As it appears in this special issue, Sharma and Giannakos (2020) summarise the state‐of‐the‐art in various learning capacities of multimodal data as well as the critical insights about MMLA in the form of a systematic literature review.…”
Section: The Promisementioning
confidence: 99%
“…That is also portrayed with the formation of the CrossMMLA SIG and the continuous growth of its respective workshops at LAK conferences (ie, Martinez‐Maldonado et al ., 2018; Spikol et al ., 2017). The contributions in this special issue cover several dimensions of these MMLA research trends, as also identified from the recent literature review of the field included in this issue (Sharma, & Giannakos, 2020). We expect and welcome further work on these dimensions and would like to conclude this editorial piece reflecting upon three main themes of challenges in MMLA research.…”
Section: Three Main Themes Of Challenges and Future Research Opportunmentioning
confidence: 99%
“…The process of collecting published studies of acceptable quality is a methodical and meticulous one. A systematic criteria need to be used for selection to reduce researcher bias and provide transparency (Bano et al., 2018; Sharma & Giannakos, 2020). We used the guidelines provided by Kitchenham and Charters (2007) to conduct our systematic review.…”
Section: Methodsmentioning
confidence: 99%
“…The selection phase determines the overall validity of the studies for the literature review, which is why it is important to define specific inclusion and exclusion criteria. We applied four quality criteria (see Appendix 2) informed by related works (Sharma & Giannakos, 2020). Therefore, studies were eligible for inclusion if they were focused on adult learning in OCOPs.…”
Section: Methodsmentioning
confidence: 99%
“…Upon completion of this process a total of 45 articles met the inclusion criteria. The manuscripts selected for detailed analysis and data extraction were divided across the readers in accordance with their field of expertise, which was carried out partially following the data extraction rubric adapted by Sharma and Giannakos [35]. The findings reported in the forthcoming sections constitute a synthesis of the research efforts that have been identified with a direct interest in facilitating PE and have been further enriched with distilled ideas for practice, policy and further research through reflection and multidisciplinary discourse.…”
Section: Methodsmentioning
confidence: 99%